Stem anatomical study of some Iranian Marrubium L. species - Sayed Mehdi Talebi; MASOUD SHEIDAI; FATEMEH ARIYANEJAD; Alex matsyura (Society for Indonesian Biodiversity, 2019)
Abstract. Talebi SM, Sheidai M, Ariyanejad F, Matsyura A. 2019. Stem anatomical study of some Iranian Marrubium L. species. Biodiversitas 20: 2589-2595. Marrubium is one of problematic genera of Lamiaceae family which distributed in different parts of Iran with 11 species. These species have been used in folk medicine for treatment of different disorders. In the present study, we used stem anatomical characteristics of six Marrubium species for taxonomical treatment of the genus and delimitation of these species. Based on the geographical distribution, one to three populations were selected from each species. Stem hand transverses were double-stained and studied using Light Microscopy. In total, sixteen qualitative and quantitative anatomical traits were studied. Anatomical data were analyzed using MVSP and SPSS software. Stems in transverse section were quadrangle, with a continuous ring of vascular tissue. The anatomical characteristics varied among the species, while the ANOVA test revealed significant variations for some of them. The studied species and their populations were divided into two groups in the UPGMA dendrogram of anatomical data. Populations of each species did not cluster together and were scattered in these groups, except those for M. cuneatum, which were clustered in only one group. Furthermore, these groups were clearly observed in PCA plot. According to CA-joined plot, each group or population had distinct anatomical feature (s) which was useful in identification of them. In some cases, the clustering pattern agreed with previous molecular and morphological studies, while in several times populations clustering did not agree with traditional classification of species as Flora of Iran and Flora Iranica. It seems that some infraspecific ranks must be redefined.